A new modified night trap: more selective and less harmful to Heterocera (Insecta: Lepidoptera) - C. Lepesqueur; S. Scherrer; L. Braga; I. Rezende-Diniz (SHILAP, 2022)
We present one modified collection container to the “Luiz de Queiroz” light trap. This night tent-trap (or NTT) is characterized by being simple, inexpensive, and efficient in several aspects related to the capture of Heterocera: 1) even the fragile insects had few morphological damages; 2) favors selective collection of specimens, avoiding the predatory capture which contributes to the maintenance of local diversity, and 3) does not select any taxonomic groups or body sizes.